Optimally and Independent Planned Microgrid with Solar-Wind and Biogas Hybrid Renewable Systems by HOMER - Mostafa Eidiani; Somayeh Mahnani (Majlesi Journal of Electrical Engineering, 2023)
Fuel shortages and environmental issues have made optimal and effective management of various resources one of the most pressing issues in the current situation. There is often a separation between the heating and gas network and the power system, which is not wise when considering the economics and effectiveness of the entire system. Examining the results shows that the installed capacity has grown significantly in the last few years. This research has investigated the microgrid including wind-solar turbine, along with energy storage (battery). This energy can be used as an alternative to fossil power plants because it is readily available and renewable. This paper proposes a multi-dimensional framework for a multi carrier energy supply with a solar-wind and biogas hybrid renewable system. In this study, the amount of power exchange of sources in a microgrid independent of the distribution network and power distribution between resources and load supply have been simulated in the HOMER environment, and the output results show the optimization of power management in this network. The proposed method is completely tested and programmed in an independent microgrid during a 24-hour period.